ANALYSIS OF THE SUCCESS OF THIRD-YEAR STUDENTS OF MEDICINE IN MEDICAL UNIVERSITY - VARNA BY TESTED ON THE CARDIOVASCULAR SYSTEM - Kosta Mirchev; Miroslav Marinov; Iglika Marinova; Borislav Boychev; Christiana Romanova; Nina Radeva; Radko Zl. Radev (Peytchinski Publishing, 2013)
The test is objective, fast and convenient way to assess student's knowledge. When used regularly, it helps rhythmic learning of school material. Students of third course year are subjected in pathophysiology test of cardiovascular system during exercise. Follow the test results for the period from 2006 to 2012: Students show a relatively very good success. Differences in each individual years are negligible. Highlighting the advantages of this method of assessment. It is recommended a wider use of test as a mean as improving quality of training of students.